Design and Implementation of a Transformer Winding Machine with Buck-Boost Converter-Based DC Motor Drive - Muhammad Rizani Rusli; Gigih Prabowo; Taufiqurrahman Taufiqurrahman; Arman Jaya; Syechu Dwitya Nugraha; Era Purwanto (Rekayasa, 2026)
This research presents the design and implementation of a high-frequency transformer winding machine driven by a DC motor with a Buck-Boost converter to produce transformers accurately and efficiently. The system integrates a DC motor controlled by a Buck-Boost converter, which regulates the voltage to the motor, ensuring stable performance during the winding process. The winding machine design includes a stable mechanical platform, a V-belt mechanism for power transmission, and optocoupler sensors for real-time monitoring of winding turns. The Buck-Boost converter stabilizes voltage fluctuations, allowing smooth motor operation under various input conditions, thereby improving machine efficiency and reliability. Experimental tests on the rectifier, Buck-Boost converter, and DC motor demonstrate high efficiency and stable performance, with minimal deviation between calculated and experimental results. Test results show that this machine can perform precise winding across different duty cycles, with optimal speed control and stable operation. Compared to existing transformer winding machines using induction motors or stepper motors, this system offers better control, faster winding speeds, and greater adaptability to different production conditions. The developed machine significantly contributes to industries such as transformer manufacturing and power electronics, with increased productivity, reduced production costs, and improved transformer quality, especially in high-frequency applications such as renewable energy systems and electric vehicle charging.